Dasar Menolak Homoseksualitas? Respons terhadap Teori Voyeurisme dalam Narasi Ham-Nuh - Rouw, Randy Frank (Indonesian Journal of Theology, 2024)
The brief narrative of Ham seeing Noah’s nakedness (Gen 9:20-27) has been interpreted by some as a text that can be used against homosexuality. This interpretation is unsurprising given the numerous exegetical traditions that characterize Ham’s action as sexual perversion, informed by a theory of voyeurism that frames Ham looking upon Noah’s nakedness with lustful desire. For such interpreters, this reading of Genesis 9:20-27 offers biblical grounds for rejecting homosexual behavior. The primary purpose of this article is to challenge the use of the Ham-Noah narrative as basis for teaching against homosexuality. This article is not necessarily written to support homosexuality but rather to examine the textual evidence through critical analysis of the term רָאָה (“to see/look”). In Genesis 34:2 and 38:15, this term is found within explicitly sexual contexts that begin with the act of looking. The textual analysis reveals significant differences between Genesis 34:2 and 38:15 and the text of Genesis 9:22 regarding רָאָה. In 34:2 and 38:15, sexual behavior is clearly recorded following the act of seeing, providing strong evidence that the uses of רָאָה in those contexts imply sexual desire. However, unlike those passages, 9:22 records no sexual behavior following the act of seeing. Therefore, it is incorrect to assert that Ham viewed Noah with sexual desire. This finding ultimately refutes the use of the Ham-Noah narrative as a basis for teaching against homosexuality.